Contribution of Oxidative Stress (OS) in Calcific Aortic Valve Disease (CAVD): From Pathophysiology to Therapeutic Targets - Daniela Maria Tanase; Emilia Valasciuc; Evelina Maria Gosav; Mariana Floria; Claudia Florida Costea; Nicoleta Dima; Ionut Tudorancea; Minela Aida Maranduca; Ionela Lacramioara Serban (Cells, 2022)
Calcific aortic valve disease (CAVD) is a major cause of cardiovascular mortality and morbidity, with increased prevalence and incidence. The underlying mechanisms behind CAVD are complex, and are mainly illustrated by inflammation, mechanical stress (which induces prolonged aortic valve endothelial dysfunction), increased oxidative stress (OS) (which trigger fibrosis), and calcification of valve leaflets. To date, besides aortic valve replacement, there are no specific pharmacological treatments for CAVD. In this review, we describe the mechanisms behind aortic valvular disease, the involvement of OS as a fundamental element in disease progression with predilection in AS, and its two most frequent etiologies (calcific aortic valve disease and bicuspid aortic valve); moreover, we highlight the potential of OS as a future therapeutic target.